Clinical small animal internal medicine - Bruyette, David; Bexfield, Nick; Chretin, Johnny D.; Kidd, Linda; Kube, Stephanie; Catherine Langston, Catherine; Owen, Tina Jo; Oyama, Mark A.; Peterson, Nathan; Reiter, Lisa V.; Rozanski, Elizabeth A.; Ruaux, Craig; et al. (Hoboken, New Jersey Wiley-Blackwell, 2020)
Clinical Small Animal Internal Medicine is a comprehensive, practical reference designed to meet the needs of veterinary practitioners and students alike. Covering all aspects of small animal internal medicine, this innovative guide provides clinically relevant material, plus podcasts and continual updates online. Concise, identically-formatted chapters allow readers to quickly find the most essential information for clinical veterinary practice"--
Includes bibliographical references and index.
Keywords: Animals -- Diseases; Domestic animals; Animals; Internal medicine; Veterinary medicine